Valorization of stainless steel slag by selective chromium recovery and subsequent carbonation of the matrix material. (20th March 2016) - Kim, E.; Spooren, J.; Broos, K.; Nielsen, P.; Horckmans, L.; Geurts, R.; Vrancken, K.C.; Quaghebeur, M.
Abstract: This study focuses on the recycling of stainless steel (SS) slags containing about 1.2 wt% of chromium (Cr). The selective recovery of Cr from SS slag by a hydrometallurgical method (alkaline pressure leaching) was investigated. Leaching experiments were carried out based on 2 4−1 factorial design of experiment (DOE) with the following parameters: NaOH concentration, temperature, leaching time, and mechanical activation (MA). Results show that temperature and MA are the most influencing factors for an enhanced Cr leaching. The maximum Cr leaching was 46% at 1 M NaOH, 240 °C, 6 h, MA 30 min, while the matrix material was dissolved only to a limited extent (Al 2.88%, Si 0.12%, Ca 0.05%). After Cr leaching followed by alkali washing, a carbonation treatment is proposed to stabilize the remaining Cr in the matrix material and make the subsequent recycling of the matrix material as a construction material possible. Highlights: Cr was selectively leached out from Cr containing slag using alkaline pressure leaching. Mechanical activation and temperature were the most important parameters for enhancing Cr leaching. The remaining matrix material can be utilized as building material after carbonation.